Cytolethal distending toxin from Glaesserella parasuis induces ferroptosis in porcine alveolar macrophages and mice - Shiyu Xu; Li Lei; Zhen Yang; Yu Wang; Senyan Du; Qin Zhao; Xiaobo Huang; Sanjie Cao; Rui Wu; Yiping Wang; Qigui Yan; Yiping Wen (Veterinary Research)
Abstract Glaesserella parasuis cytolethal distending toxin (GpCDT) is a bacterial genotoxin whose main action is to activate DNA damage responses, induce cell cycle arrest, and induce the apoptosis of host cells. In our previous studies, we reported that cells incubated with GpCDT exhibited changes in the expression of ferroptosis-related proteins; thus, we hypothesized that, in addition to apoptosis, GpCDT may also cause ferroptosis, a novel mode of cell death. Here, we observed that treatment of 3D4/21 cells with GpCDT resulted in cytoplasmic iron overload, depletion of GSH (reduced glutathione), and overproduction of reactive oxygen species (ROS) and malondialdehyde (MDA), indicating that GpCDT disrupted iron metabolism and redox homeostasis in these cells. These phenomena were counteracted by the specific ferroptosis inhibitor ferrostatin-1 and the iron chelator deferoxamine mesylate. In vitro infection with the Glaesserella parasuis field isolate strain SC1401 (CDT positive) induced changes in the expression of ferroptosis biomarkers and proteins. Infection of C57BL/6 mice yielded similar results. Our results suggest that ferroptosis may play a substantial role in GpCDT-induced cellular injury.